Reflective equilibrium on the fringe : The tragic threefold story of a failed methodology for logical theorising - Dicher, Bogdan (2020)
Reflective equilibrium, as a methodology for the ‘formation of log- ics’, fails on the fringe, where intricate details can make or break a logical the- ory. On the fringe, the process of theorification cannot be methodologically governed by anything like reflective equilibrium. When logical theorising gets tricky, there is nothing on the pre-theoretical side on which our theoretical claims can reflect of—at least not in any meaningful way. Indeed, the fringe is exclusively the domain of theoretical negotiations and the methodological power of reflective equilibrium is merely nominal.